(untitled) (Bangladesh Journal of Botany, 2020)
Antimicrobial activity of leaves of Verbascum thapsus L. using different extractions solvents was evaluated. Extracts were prepared and tested against different bacterial (Pseudomonas aeruginosa, Klebsiella pneumoniae, Bacillus atrophaeus, Salmonella typhi, Citrobacter freundii and fungal species (Alternaria solani, Candida albicans, Aspergillus fumigatus). Disc and well diffusion assays were used for screening antibacterial and antifungal potential of extracts. The ethyl acetate extract produced the maximum zone of inhibition (70% ZI) against K. pneumoniae at 3000 μg/disc. Methanol extracts formed 68% ZI against S. typhi, 54% ZI against A. tumefacian and 50% ZI against C. freundii, respectively at 3000 μg/disc respectively. Against the fungal species, the methanol extract was effective and formed maximum zone of inhibition (50% ZI) against A. solani at 3000 μg/well. Hexane extract was moderately active against bacterial species but inactive against tested fungal species. T. rubrum was resistant and none of the tested extracts affected its growth.